Arterial hypertension in chronic kidney disease: current state of the problem - T. V. Zueva; T. V. Zhdanova (Лечащий Врач, 2021)
Arterial hypertension (AHT) is a significant problem in the healthcare system. It is a major modifiable risk factor for cardiovascular disease (CVD), stroke, and renal failure. Long-term and persistent hypertension accelerates the progression of kidney disease to the terminal stage, and a progressive decline in renal function, on the contrary, increases blood pressure (BP) and worsens its control. Chronic kidney disease (CKD) is both a common cause of hypertension and a complication of uncontrolled hypertension. Hypertension and CKD are closely related by mixed causal relationships. Because hypertension can be a cause and effect of CKD, its prevalence is higher and more difficult to control. The interaction between hypertension and CKD is complex and increases the risk of adverse cardiovascular and cerebrovascular outcomes. The pathophysiology of hypertension in CKD is complex and is a consequence of many factors, including decreased nephron mass, increased sodium retention and expansion of extracellular volume, overactive sympathetic nervous system, activation of hormones, including the renin-angiotensin-aldosterone system, and endothelial dysfunction. Patients with CKD are more likely to have high-risk hypertension: latent, resistant and nocturnal hypertension. This literature review is devoted to modern concepts of the prevalence, pathogenesis, course, control, principles of hypertension treatment in CKD. The urgency of this problem is associated with an increase in the number of patients with hypertension and CKD worldwide and their high morbidity and mortality. The bi-directional nature of the relationship between hypertension and CKD makes it promising to study these two conditions in order to slow the rate of progression of renal and cardiac dysfunction.